Opportunities and limitations for the production of safe fermented meats without nitrate and nitrite using an antibacterial Staphylococcus sciuri starter culture. (November 2016) - Sánchez Mainar, María; Xhaferi, Ramize; Samapundo, Simbarashe; Devlieghere, Frank; Leroy, Frédéric
Abstract: The ability of the meat isolate Staphylococcus sciuri I20-1 to inhibit food-borne pathogens in view of its application as a functional starter culture for the production of clean-label fermented meats was investigated. The strain produced a heat-stable antibacterial compound of a proteinaceous nature that was released following primary metabolite production kinetics. Its specific inhibitory spectrum included different strains of Staphylococcus aureus and both vegetative cells and spores of Clostridium botulinum . These two species pose potential biosafety hazards, in particular when producing fermented meats with a mild pH and without added nitrate and nitrite salts. Up till now, starter-culture based strategies to restrain S. aureus and C. botulinum have barely been explored in fermented meats, in contrast to the frequently investigated use of antilisterial cultures of lactic acid bacteria. When added to a fermented sausage model, S. sciuri I20-1 acted as a persistent culture throughout the fermentation process, during which it was able to produce its antibacterial compound in situ . In co-culture experiments, an immediate two-log inactivation of a S. aureus strain was found, even before production of the antibacterial compound could be detected. This was probably due to an instant pH-driven desorption of the antibacterial molecules from the producer cells when added to the meat batter. However, a sub-population of S. aureus that was resistant to the antibacterial compound was able to grow out to the same final counts as in the control experiment performed with a non-inhibitory strain of S. sciuri . This finding is indicative of the potential pitfalls when extrapolating promising in vitro results to the true complexity of fermented food matrices. Highlights: Production of a bacteriocin-like substance by Staphylococcus sciuri I20-1. Activity towards Staphylococcus aureus and Clostridium botulinum (incl. spores). In situ production of the antibacterial compound during meat fermentation. Rapid pH-driven detachment of the antibacterial compound from the producer cells. In situ inactivation of S. aureus but followed by regrowth of resistant cells.